PROSES PEMBENTUKAN KATA PADA LIRIK LAGU TULUS DALAM ALBUM MANUSIA: KAJIAN MORFOLOGIS - Siti Dwy Candra Muslikah; I Made Madia; I Wayan Teguh (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to describe (a) the types of affixation in the lyrics of the song Tulus in the album Human, (b) the types of reduplication in the lyrics of the song Tulus in the album Human, (c) the types of compounding in the lyrics of the song Tulus in the album Human, (d) types of cliticization in the lyrics of the song Tulus in the album Human, and (e) the peculiarities of form and meaning in the lyrics of the song Tulus in the album Human. This type of research is qualitative research with the data source in the form of song lyrics. The data collection methods and techniques used in this research are the observation method with note-taking techniques, the data analysis methods and techniques used are the agih method with basic techniques in the form of techniques for direct elements, as well as the methods and techniques for presenting the results of data analysis in the form of formal, informal methods with techniques. descriptive. The results of this research include the types of affixation found totaling 95 data, the types of affixation combining with other forms totaling 22 data, the types of reduplication found totaling 10 data, the types of compounding found totaling 4 data, and the types The cliticizations found amounted to 38 data. Apart from that, there were typical word forms and meanings found totaling 9 pieces of data.